College student sleep and executive functioning: An examination of potential moderators - Cifre, Anthony B.; Walters, Kenneth S.; Budnick, Christopher J. (Translational Issues in Psychological Science, 2020)
Approximately 60% of college students report sleep disturbances. Sleep disturbances, such as insomnia, negatively influence physical energy, cognitive resources, and affective states that might inhibit executive functioning. To better delineate the variables that alter the college student insomnia and executive functioning relationship we examined sleepiness, sleep debt, and attention-deficit/hyperactivity disorder (ADHD) symptomatology. We expected insomnia to predict executive dysfunction, with a stronger relationship observed at higher levels of the focal moderator (i.e., sleepiness, sleep debt, or ADHD symptoms). Undergraduate participants (n = 472) completed a cross-sectional survey assessing insomnia, state sleepiness, sleep debt, ADHD symptomatology (inattention, hyperactivity, and impulsivity), and executive dysfunction. Hierarchical linear regressions showed that poor sleep had a negative influence on executive function when college students also had high levels of impulsivity, state sleepiness, or sleep debt. These results partially support our expectations and further the academic sleep-related literature while providing insight for counselors, academic advisors, or other professionals working with college student populations. (PsycInfo Database Record (c) 2020 APA, all rights reserved)
Keywords: Attention Deficit Disorder with Hyperactivity; College Students; Executive Function; Financial Strain; Insomnia; Sleep; Sleepiness; Symptoms; dept.psy; peer-reviewed